Pendampingan Pembuatan Video Cerita Rakyat „Batu Badaong“ dalam Pembelajaran Bahasa Jerman (Kolaborasi Mahasiswa Khon Khaen Thailand dan Mahasiswa Universitas Pattimura Ambon) - Lestuny, Caroline; Noya van Delzen, June Carmen (German für Gesellschaft (J-Gefüge), 2024)
Learning a language means learning culture. Language and culture are two things that cannot be separated. Culture contains many components, including regional folklore. Folklore needs to be known not only by local communities but also at national and international levels. As an institution that produces professional output, the Faculty of Teacher Training and Education at Pattimura University needs to contribute to future development. One of the activities that can be carried out is by providing assistance in making videos of the Batu Badaong folklore in German. This activity involved 4 foreign students, namely from Khong Kaen University, Thailand and 7 students from the German language education study program at Pattimura University, Ambon. The methods used in this activity are varied, namely lectures, discussions and simulations. The result of this activity is a short film about Batu Badaong in German which can be seen at https://youtu.be/OfGDZw1jNJQ.